(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: The role of uric acid in the progression of prediabetes to diabetes has been known. Serum uric acid has been shown to beassociated with cardiovascular disease, hypertension, and chronic kidney disease. However, conflicting data exist asregards the serum uric acid (UA) levels in type 2 diabetes mellitus, which are associated with risk factors andcomplications. Material & Methods: The present study was designed to look for any association of serum uric acid with hypertension in type 2diabetes mellitus, taking into consideration the relevant clinical, biochemical and the anthropometric data. 110 patientswith type 2 male diabetes mellitus as case and 100 healthy malecontrols were included in this study. Results: This study shows that there were significant differences in mean of age, duration of DM, exercise time, waist hip ratio, systolic blood pressure and diastolic blood pressure within case and control but no significant differences of mean BMI was found between and control. The mean age, duration of DM, exercise time, waist hip ratio, systolic blood pressure and diastolic blood pressure and BMI were (51.83±9.911 years, 6.87±5.54 years, 1.94±.831 hours, .92±.03, 140±6.75 mm of Hg,90±2.41 mm of Hg and 25.43±3.19 Kg/m2 respectively), where as in controls these were (44.81±9.66 yrs, 00 years, 1.12±.327 hours, .91±.03, 130±1.28 mm of Hg, 80±6.18 mm of Hg and 24.96±3.02 Kg/m2 respectively). This table also shows that significant differences in mean of FBS, ABF, HbA1C and S. Uric acid between case and control, but there was no significant differences of mean TG, Cholesterol, HDL and LDL. The mean of FBS, ABF, HbA1C and S. Uric acid among the cases were (8.19±2.48 mmol/L, 11.29±3.47 mmol/L, 7.96±6.04 mg%, 189.72±111.36 mg/dl, 179±43 mg/dl, 38.38±13.77 mg/dl, 102.10±35.79 mg/dl and 8.39±2.61 mg/dl respectively, on the other hand among the control these were 5.91±1.13 mmol/L, 9.19±1.95 mmol/L, 5.93±1.01 mg%, 200±104.49 mg/dl, 183±42.25 mg/dl, 38.14±5.52 mg/dl, 110±33.23 mg/dl and 5.14±.84 mg/dl respectively. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 96-101